Challenges of Diversity : Essays on America. - Sollors, Werner (Rutgers University Press, 2018)
What unites and what divides Americans as a nation? Opening with a survey of American literature through the vantage point of ethnicity, Werner Sollors examines the changing self-understanding of the United States from an Anglo-American to a multicultural country and the role writing has played in that process.